2014
DOI: 10.18632/oncotarget.1959
|View full text |Cite
|
Sign up to set email alerts
|

JG6, a novel marine-derived oligosaccharide, suppresses breast cancer metastasis via binding to cofilin

Abstract: Cofilin, an actin-binding protein which disassembles actin filaments, plays an important role in invasion and metastasis. Here, we discover that JG6, an oligomannurarate sulfate, binds to cofilin, suppresses the migration of human breast cancer cells and cancer metastasis in breast cancer xenograft model. Mechanistically, JG6 occupies actin-binding sites of cofilin, thereby disrupting cofilin modulated actin turnover. Our results highlight the significance of cofilin in cancer and suggest JG6, a cofilin inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Significant future work will be needed to test this hypothesis and validate the functionality of DSLS in vivo. Given numerous gap junction-inhibitors and the discovery of cofilin-binding oligosaccharide JG6, itself shown to be capable of suppressing lung metastasis in mice, there may be a future translation of this data to the prevention or suppression of bone metastasis 40,41 . We realize that morphological evidence may not be sufficient to support the uniqueness of DSLSit might indeed be molecularly related to one of these previously described structures.…”
Section: Discussionmentioning
confidence: 99%
“…Significant future work will be needed to test this hypothesis and validate the functionality of DSLS in vivo. Given numerous gap junction-inhibitors and the discovery of cofilin-binding oligosaccharide JG6, itself shown to be capable of suppressing lung metastasis in mice, there may be a future translation of this data to the prevention or suppression of bone metastasis 40,41 . We realize that morphological evidence may not be sufficient to support the uniqueness of DSLSit might indeed be molecularly related to one of these previously described structures.…”
Section: Discussionmentioning
confidence: 99%
“…In migrating or invading cells, cofilin resides in cell membrane protrusions, for example lamellipodia, invadopodia, and filopodia, which initiate cell movement and determine cell polarity ( 36 , 37 ). This localization is critical for cell movement, endocytosis and cell division, all of which are important for normal cell proliferation, differentiation and cancer development ( 38 ). This promotion may be responsible for the positive association between cofilin expression and NHG, Her2 and Ki-67 status.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that cofilin promotes invadopodial membrane recycling during cell invasion (11). Moreover, cofilin has been demonstrated to act as a key regulator in cancer cell motility (26,27). For instance, Chen et al (28) showed that cofilin was a critical signaling pathway involved in miR-138-mediated ovarian cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 99%